On Strong Pre*-I-Open Sets in Ideal Topological Spaces - Ahlam Abdullah Bin Kuddah; Radhwan Mohammed Aqeel (Journal of New Theory)
The aim of the present paper is to introduce the class of strong pre*-I-open sets which is strictly placed between the class of all pre-I-open and the class of all pre*-I-open subsets of X. Relationships with some other types of sets were given. Furthermore, by using the new notion, we defined the strong pre*-I-Interior and strong pre*I-closure operators and established their various properties.